Pemetaan Dinamika dan Tantangan Peran FKUB Rejang Lebong dalam Kerukunan Beragama - Purnamasari, Elvira; Zikri, M.; Saputra, Jeni Harlen (Al-DYAS, 2026)
Religious harmony in multicultural settings is determined not only by the absence of open conflict, but also by institutional capacity to manage differences in a sustainable manner. The Forum Kerukunan Umat Beragama (FKUB) of Rejang Lebong Regency faces several challenges, including low diversity literacy at the grassroots level, budget dependence on the local government, limited youth regeneration, and weak adaptation to challenges in the digital sphere. This study aimed to map the dynamics and challenges of the role of FKUB Rejang Lebong in maintaining interreligious harmony. A descriptive qualitative approach was employed, using passive observation during the Praktik Pengalaman Lapangan (PPL) program activities, semi-structured interviews with FKUB board members and religious leaders, and institutional document analysis. The findings show that FKUB Rejang Lebong plays a strategic role as a mediator in conflicts related to houses of worship, a facilitator of interfaith dialogue, and a provider of technical recommendations for licensing; however, the effectiveness of these roles is constrained by dependence on grant-based funding, low youth participation in the Forum Pemuda Lintas Agama (FPLA), and the limited production of narratives of religious moderation in the digital sphere. The study concludes that harmony in Rejang Lebong remains at the level of negative peace, thus requiring more inclusive and participatory institutional strengthening to achieve substantive harmony. The implications of this research include recommendations for the application of an Asset-Based Community Development (ABCD) approach and the enhancement of digital literacy and strategies to reinforce the role of FKUB in responding to contemporary socio-religious dynamics.